Effects of Natura 2000 and habitat variables used for habitat assessment on beetle assemblages in European beech forests. Issue 3 (15th November 2014) - Zehetmair, Tobias; Müller, Jörg; Zharov, Alexey; Gruppe, Axel; Leather, Simon R.
Abstract The Natura 2000 (N2000) network intends to conserve Europe's threatened habitats and species by selecting a complementary set of areas of various habitat types across geographical space to cover the range of diversity. We studied beetles and habitat variables used for N2000 habitat assessment in 11 pairs of commercially exploited N2000 and non‐N2000 forest stands (80–120 years old) of one habitat type (9130 Asperulo‐Fagetum) in three biogeographical regions (Atlantic, Continental, Mediterranean). We addressed three main questions: (i) Is beetle diversity affected by climatic, spatial and structural variables and how? (ii) Does N2000 status affect beetle diversity and habitat quality? (iii) Are the habitat variables used for N2000 habitat assessment decisive for beetle communities? Climate and spatial variables had the largest impacts on beetle communities which supports the value of N2000 as a transnational network of protected areas over different climatic conditions. Forest structures had a minor cumulative impact on beetle assemblages. N2000 had no effects on beetle diversity or forest structures. We conclude that these commercially exploited N2000 stands do not presently represent better habitats relative to the commercially exploited non‐N2000 stands. However, significant effects on beetle communities were found for 'beech proportion', 'tree species', 'forest layering', 'deadwood' and 'habitat trees', which confirms the suitability of these parameters for habitat assessment in the N2000 process. We conclude that additional efforts are required in N2000 areas (e.g. implementation of specific management plans) to develop and ensure an ecologically effective and sustainable network to preserve Europe's biodiversity.